2019
DOI: 10.1007/s10973-019-08512-1
|View full text |Cite
|
Sign up to set email alerts
|

Surface tension of ethylene glycol-based nanofluids containing various types of nitrides

Abstract: This paper focuses on an experimental study of the surface tension of nanofluids based on ethylene glycol with various types of nitride nanoparticles. Samples were prepared using a two-step method with mass content between 1 and 5% of particles. Nanofluids contain three types of nitride nanoparticles: aluminum nitride, silicon nitride and titanium nitride with various particle average sizes. Surface tension of nanofluids was investigated at a constant temperature of 298.15 K with two different techniques: du N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Reductions in SFT were obtained for the two nano-diamond nanopowders (nD87 and nD97), while slight increases were observed for dispersions prepared using the other three carbon-based nanopowders. However, it must be pointed out that, except for results obtained for 1.0% concentrations of nD87/PEG and nD97/PEG sets using the Du Noüy ring method and 1.0% loading of nD87/PEG using the drop-shape analyzer, all modifications are within the experimental uncertainties reported by these devices 1.0% [93].…”
Section: Surface Tensionmentioning
confidence: 70%
See 3 more Smart Citations
“…Reductions in SFT were obtained for the two nano-diamond nanopowders (nD87 and nD97), while slight increases were observed for dispersions prepared using the other three carbon-based nanopowders. However, it must be pointed out that, except for results obtained for 1.0% concentrations of nD87/PEG and nD97/PEG sets using the Du Noüy ring method and 1.0% loading of nD87/PEG using the drop-shape analyzer, all modifications are within the experimental uncertainties reported by these devices 1.0% [93].…”
Section: Surface Tensionmentioning
confidence: 70%
“…In this case, determinations were performed using a ring with a radius of 9.691 mm and made of a platinum-iridium wire (0.203 mm in radius). Previous surface tension studies performed for substances of well-known SFT with this same Du Noüy tensiometer showed deviations within 1% [93]. Further details about the principles of both techniques and the followed experimental procedures can be found in Wanic et al [93].…”
Section: Thermal and Physical Characterizationmentioning
confidence: 93%
See 2 more Smart Citations
“…Thermophysical behavior of graphene-based nanofluids has been the topic of several investigations [17][18][19]. However, so far, analysis and evolution of the surface tension (ST) of graphene-based nanofluids, which is another important aspect to take into account in nanofluid behavior, has been overlooked [20].…”
Section: Introductionmentioning
confidence: 99%